Influência da obesidade sobre as morfologias de onda da pressão intracraniana e cerebral: um estudo prospectivo - Marine, Diego Adorna (Universidade Federal de São Carlos, 2021)
Introduction: Obesity is a low-grade inflammatory disease, which can lead to the development of other pathologies, such as diabetes mellitus, dyslipidemias and arterial hypertension (AH). Compare the relationship between blood pressure (BP) and intracranial pressure (ICP), given by the cerebral perfusion pressure, AH can cause an increase in ICP. The increase in ICP is related to stroke, migraines, ocular hypertension, among other pathologies. Thus, the aim of this study was to analyze the behavior of the ICP wave morphology in the face of obesity, to analyze the non-invasive form and to prospect for information about AH, ICP, inflammatory and metabolic aspects, and cerebral morphology in Wistar rats. Materials and methods: Two parallel studies were carried out, with a 24-week treatment of a high-fat diet, to induce obesity, after a previous adaptation of 60 days, with a standard diet. In study 1, 16 rats were divided into the Obese (OB, n = 9) and Non-Obese (NOB, n = 7) groups. All animals were adopted every 4 weeks, being: Fat percentage (% g), Body mass (BM), Fat free mass (FFM), Bone mineral content (BMC), BP, Heart rate (HR) and ICP. In study 2, 61 animals were divided into the groups, high-fat diet (HFD) and chow diet (CD) and subdivided by weeks in which they were sacrificed, over the 24 weeks (W0, W8, W16, W24). Group OB and W-HFD were fed with HFD and NOB and W-CD with CD. The evaluations of the non-invasive variables were carried out in study 2 every 8 weeks, and part of the animals being sacrificed. Also extracted were: brain weight, brain lipid content, number of cells in the primary motor area (M1), the thickness of the gray matter in this area, in addition to blood glucose, lipid profile, and inflammatory profile. Euthanasia took place every 8 weeks in study 2, and in study 1 at the end of 24 weeks. Results: Study 1 statistical difference in the area under the ICP curve, between OB and NOB, with a reduction in the NOB group, remaining below OB during treatment. In study 2, there was no difference between the groups, only was a probability of an increase in the W24-HFD group. Regarding BP, no statistical difference was found in both studies. However, HR was statistically different in study 1, being higher in OB, and the probability of increase in study 2. BM,%fat, FFM, and BMC were higher in the OB and W24-HFD groups, compared to the control. There is no difference in brain lipid content or relative brain weight at the end of treatment. There was a probability of a decrease in brain weight in the HFD groups, and also a decrease in the total number of M1 cells, in addition to an increase in the thickness of the gray matter of this same area in the HFD group. Discovery of decreased brain-derived neurotrophic factor (BDNF), and increased leptin at the end of treatment in the W24-HFD group. Conclusion: The HFD developed obesity in rats, but did not promote dyslipidemia or chronic inflammation. The increase in blood glucose in the OB group demonstrates possible insulin resistance. Variations in ICP are due to the better cerebral compliance of the NOB group. An increased likelihood of leptin, gray matter thickness, loss of cell number and reduction of circulating BDNF levels may indicate loss of neural plasticity, glial cells, and increased fluid in the brain parenchyma. This scenario may be the beginning of a greater damage to the brain, potentially leading to an increase in the PIC.
Influence of obesity on the pressure wave morphologies intracranial and brain: a prospective study
Keywords: Pressão intracraniana; Hipertensão; Obesidade; Inflamação; Intracranial pressure; Hypertension; Obesity; Inflammation; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA GERAL